Non-peptidic glucose-like peptide-1 receptor agonists: aftermath of a serendipitous discovery - Wang Ming-wei; Liu Qing; Zhou Cai-hong (Acta Pharmacologica Sinica, 2016)
Glucagon-like peptide-1 (GLP-1) receptor is an ideal target in the development of incretin-based therapies for diabetes and obesity. Two approaches have been adopted: GLP-1 receptor agonists that mimic the effects of native GLP-1 and dipeptidyl peptidase-4 inhibitors that increase endogenous GLP-1 levels. During the past two decades, search for orally active, non-peptidic GLP-1 receptor agonists has been the focal point of research and development activities in many multinational pharmaceutical companies. Such efforts have not resulted in any success thus far. Serendipitous discovery of substituted cyclobutanes represented by Boc5 as a new class of GLP-1 receptor agonists led us to believe that a small molecule approach to class B G-protein coupled receptor agonism is no longer a fantasy but a reality. However, major obstacles still pose great challenges, and the reasons of which are discussed in this perspectives.